Binding Specificity of Two PBPs in the Yellow Peach Moth Conogethes punctiferalis (Guenée) - Ge, Xing; Ahmed, Tofael; Zhang, Tiantao; Wang, Zhenying; He, Kanglai; Bai, Shuxiong (Frontiers in Physiology, 2018)
Pheromone binding proteins (PBPs) play an important role in olfaction of insects by transporting sex pheromones across the sensillum lymph to odorant receptors. To obtain a better understanding of the molecular basis between PBPs and semiochemicals, we have cloned, expressed, and purified two PBPs (CpunPBP2 and CpunPBP5) from the antennae of Conogethes punctiferalis. Fluorescence competitive binding assays were used to investigate binding affinities of CpunPBP2 and CpunPBP5 to sex pheromone and volatiles. Results indicate both CpunPBP2 and CpunPBP5 bind sex pheromones E10-16:Ald, Z10-16:Ald and hexadecanal with higher affinities. In addition, CpunPBP2 and CpunPBP5 also could bind some odorants, such as 1-tetradecanol, trans-caryopyllene, farnesene, and β-farnesene. Homology modeling to predict 3D structure and molecular docking to predict key binding sites were used, to better understand interactions of CpunPBP2 and CpunPBP5 with sex pheromones E10-16:Ald and Z10-16:Ald. According to the results, Phe9, Phe33, Ser53, and Phe115 were key binding sites predicted for CpunPBP2, as were Ser9, Phe12, Val115, and Arg120 for CpunPBP5. Binding affinities of four mutants of CpunPBP2 and four mutants of CpunPBP5 with the two sex pheromones were investigated by fluorescence competitive binding assays. Results indicate that single nucleotides mutation may affect interactions between PBPs and sex pheromones. Expression levels of CpunPBP2 and CpunPBP5 in different tissues were evaluated using qPCR. Results show that CpunPBP2 and CpunPBP5 were largely amplified in the antennae, with low expression levels in other tissues. CpunPBP2 was expressed mainly in male antennae, whereas CpunPBP5 was expressed mainly in female antennae. These results provide new insights into understanding the recognition between PBPs and ligands.